A ditadura brasileira no tempo: um estudo dos discursos do jornal O Globo em 1964/1985 e 2014 - Costa, Edwaldo (2014)
The journalistic speech articulate themselves in dynamic way and consist themselves in part of generating elements from the cultural history of nation. This research investigates as part of the Brazilian Dictatorship speech which was revival and narrated by the O Globo Journal, during the period of 1964 to 1985, and still up to now in 2014, when the military coup completed 50 years old. Approaching to this context about the Brazilian dictatorship time, the O Globo Journal it is not portraited real events, however, rebuilt and interpreted the facts using to discursive strategies to affirm their choices. Moreover, this academic research does not have ideological bias and, therefore, does not intend to defend military and leftist groups. However, it seeks to analyze the main features of the speech served on the newspaper in quest examinated to know whether the O Globo supported the Brazilian Dictatorship, if there was some changing on the spoke discourse retold by the newspaper along the years, and however, if Mr. Roberto Marinho has got some benefit himself in any moment support provided by the military, if there was unworthiness of the guerrillas against the newspaper and to generate hatred for them. This research seeks to complete the identification of O Globo editorial directions. The pragmatic analysis of the journalistic discourse allows to studying the linguistic and extra-linguistic context - discourse, situational - elucidating the intention embedded on the pages of the printed newspaper. So, the discursive features were evaluated throughout the goal of reconstructing the strict logic of the subject within the fragmented universe of journalism